1998
DOI: 10.1128/jvi.72.1.796-801.1998
|View full text |Cite
|
Sign up to set email alerts
|

Transient Viral DNA Replication and Repression of Viral Transcription Are Supported by the C-Terminal Domain of the Bovine Papillomavirus Type 1 E1 Protein

Abstract: The bovine papillomavirus type 1 E1 protein is important for viral DNA replication and transcriptional repression. It has been proposed that the full-length E1 protein consists of a small N-terminal and a larger C-terminal domain. In this study, it is shown that an E1 polypeptide containing residues 132 to 605 (which represents the C-terminal domain) is able to support transient viral DNA replication, although at a level lower than that supported by the wild-type protein. This domain can also repress E2-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The data presented in this study on the ability of the E1C cDNA to reduce E2-mediated transrepression are consistent with previous observations showing that an E1 polypeptide spanning the C-terminal domain of bovine papillomavirus type 1 (residues 132–605) is able to repress E2-mediated transactivation of the viral p89 promoter (Ferran & McBride, 1998 ). Further studies of E1C transactivation and modulation of E2 transrepression are needed.…”
Section: Discussionsupporting
confidence: 92%
“…The data presented in this study on the ability of the E1C cDNA to reduce E2-mediated transrepression are consistent with previous observations showing that an E1 polypeptide spanning the C-terminal domain of bovine papillomavirus type 1 (residues 132–605) is able to repress E2-mediated transactivation of the viral p89 promoter (Ferran & McBride, 1998 ). Further studies of E1C transactivation and modulation of E2 transrepression are needed.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the central and C-terminal regions of E1 contain the ATPase and helicase domains, although the boundaries are not well defined (MacPherson et al , 1994 ; Mansky et al , 1997 ; Sarafi & McBride, 1995 ; Yang et al , 1993 ). Interestingly, none of these mapped activities requires E1 sequences in the N-terminal 80 amino acids, and if this region is deleted entirely the protein still has some replication function (Ferran & McBride, 1998 ). In order to address possible roles for the N-terminal region, all available papillomavirus E1 protein predicted amino acid sequences were examined for conserved sequences.…”
Section: Resultsmentioning
confidence: 99%
“…From the above reports, it is apparent that the E1 protein is multifunctional and has complex regulation mediated through both post-translational modification and protein–protein interactions. Mutational studies map most E1 functions to the central and C-terminal portions of the protein and it has been reported that deletion of the first 131 amino acids yields an E1 protein that retains replication capacity, though at a reduced level (Ferran & McBride, 1998 ). In order to evaluate possible functional contributions of the N-terminal region, we previously compared the available E1 sequences for conserved features within the first 100 amino acids (McShan & Wilson, 1997 a ).…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal domain of E1 is only required for replication in vivo (Ferran and McBride, 1998;Sun et al, 1998) and likely plays a role in regulating intracellular localization. The E1 protein shuttles from the nucleus to the cytoplasm and the N-terminal domain contains both nuclear import and export signals that are regulated by cyclin A/E-Cdk2 (Deng et al, 2004;Hsu et al, 2007;Lentz et al, 1993;Ma et al, 1999).…”
Section: A the E1 Initiator Proteinmentioning
confidence: 99%